Characterization, antibacterial and toxicity evaluation of biosynthesized zinc oxide nanoparticles utilizing Eleuthrine bulbosa bulb extract - Norazalina Saad; Che Azurahanim Che Abdullah; Nurul Athikah Adila Zainal; Albert, Emmellie Laura (Penerbit Universiti Kebangsaan Malaysia, 2023)
In the current study, Eleuthrine bulbosa bulb extract was utilized to synthesize zinc oxide nanoparticles (ZnO NPs) in a simple, sustainable, and environmentally friendly manner. The bioactive compounds of E. bulbosa extract were identified by gas chromatography-mass spectrometry (GC-MS). Following synthesis of the ZnO NPs via the green method with E. bulbosa bulb extract as the reducing and capping agent, ZnO NPs were characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet-Visible Spectroscopy (UV-Vis), and Photoluminescence (PL) further evaluated for antibacterial and cytotoxic activities. GC-MS analysis showed the presence of phytochemical compounds acting as reducing and capping agents. The UV-Vis spectra of ZnO nanoparticles containing E. bulbosa extract showed an optical energy bandgap between 3.12 and 3.89 eV. In addition, XRD showed that the crystalline size of ZnO NPs ranged from 21 to 68 nm with a wurtzite crystal structure. FTIR analysis showed that the plant extract contains identified functional groups including alcohols, phenols, alkene, and flavonoid compounds that influenced the mechanism of bonding with ZnO NPs. Particularly, the peaks of formation of Zn-O stretching vibrations at 470 to 480 cm-1 were successfully shown. In addition, ZnO NPs displayed antibacterial activity, which was greatest against Staphylococcus aureus, and were cytotoxic to MCF-7 and MCF-10A breast cells with IC50 values of 5.540 µg/mL and 15.77 µg/mL, respectively. ZnO NPs were successfully synthesized utilizing a green method, resulting in intriguing biocompatible potential candidates for use in both biomedical and environmental fields due to their eco-friendly synthesis and nontoxic.